2022
DOI: 10.1097/mpa.0000000000002048
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up and Immunomonitoring of Relapsing Type 1 Autoimmune Pancreatitis Treated With Rituximab

Abstract: Objectives: To evaluate the efficacy and safety of rituximab in relapsing type 1 autoimmune pancreatitis especially the long-term clinical and immunologic impacts.Methods: All consecutive patients with type 1 autoimmune pancreatitis were retrospectively included. The rituximab protocol was induction therapy of 375 mg•m −2 intravenous weekly for 4 weeks, followed by 500 mg intravenous every 6 months for 2 years. The follow-up included clinical examinations, biological tests, positron emission tomography scan, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Hart et al (42) reported rituximab as a treatment for recurrent AIP. A decrease in serum IgG4 concentration and the extinction of pancreatic hypermetabolic signal on positron emission tomography were achieved in type 1 AIP after rituximab treatment (43). Other therapies for type 1 AIP, including rilzabrutinib (Bruton tyrosine kinase inhibitor), belimumab (B-cell activating factor inhibitor), and inebilizumab (anti-CD19 monoclonal antibody), are under investigation (44).…”
Section: Discussionmentioning
confidence: 99%
“…Hart et al (42) reported rituximab as a treatment for recurrent AIP. A decrease in serum IgG4 concentration and the extinction of pancreatic hypermetabolic signal on positron emission tomography were achieved in type 1 AIP after rituximab treatment (43). Other therapies for type 1 AIP, including rilzabrutinib (Bruton tyrosine kinase inhibitor), belimumab (B-cell activating factor inhibitor), and inebilizumab (anti-CD19 monoclonal antibody), are under investigation (44).…”
Section: Discussionmentioning
confidence: 99%